Prophylactic Resorbable Synthetic Mesh to Prevent Wound Dehiscence and Incisional Hernia in High High-risk Laparotomy: A Pilot Study of Using TIGR Matrix Mesh - Söderbäck, Harald; Mahteme, Haile; Hellman, Per; Sandblom, Gabriel (Frontiers in Surgery, 2016)
Background Wound dehiscence and incisional hernia are potentially serious complications following abdominal surgery, especially if performed through a midline incision. Although prophylactic reinforcement with on-lay mesh has been shown to reduce this risk, a permanent mesh carries the risk of seroma formation, infection, and persistent pain. The aim of this study was to assess the safety of a reabsorbable on-lay mesh to reinforce the midline suture in patients with high risk for wound dehiscence or incisional hernia. Method Sixteen patients with three or more risk factors for wound dehiscence or incisional hernia were included. A TIGR® Matrix mesh, composed of a mixture of 40% copolymer fibers of polyglycolide, polylactide, and polytrimethylene carbonate and 60% copolymer fibers of polylactide and polytrimethylene carbonate, was placed on the aponeurosis with an overlap of five on either side and fixated with continuous monofilament polydioxanone suture. All postoperative complications were registered at clinical follow-up. Results Mean follow-up was 9 months. One patient developed a seroma that needed drainage and antibiotic treatment. One patient had a wound infection that needed antibiotic treatment. There was no complication requiring a reoperation. No wound dehiscence or incisional hernia was seen. Conclusion On-lay placement of TIGR® Matrix is safe and may provide a feasible way of reinforcing the suture line in patients with high risk for postoperative wound dehiscence or incisional hernia. Larger samples are required, however, if one is to draw any conclusion regarding the safety and effectiveness of this technique.